2024
DOI: 10.1186/s40035-023-00388-4
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of VEGF function by bevacizumab alleviates early-stage cerebrovascular dysfunction and improves cognitive function in a mouse model of Alzheimer’s disease

Min Zhang,
Zhan Zhang,
Honghong Li
et al.

Abstract: Background Alzheimer's disease (AD) is a neurodegenerative disorder and the predominant type of dementia worldwide. It is characterized by the progressive and irreversible decline of cognitive functions. In addition to the pathological beta-amyloid (Aβ) deposition, glial activation, and neuronal injury in the postmortem brains of AD patients, increasing evidence suggests that the often overlooked vascular dysfunction is an important early event in AD pathophysiology. Vascular endothelial growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 127 publications
1
2
0
Order By: Relevance
“…However, studies of VEGF treatment in mice are inconsistent. One study found that blocking VEGF signaling in AD mice leads to better cognitive function [19], while another study found that VEGF treatment led to better cognitive function in mice [5]. In the context of Robo4, our data and previous studies suggest that the impact of VEGF treatment, whether positive or negative in AD, might depend on the status of Robo/Slit signaling.…”
Section: Vegf and Adsupporting
confidence: 56%
“…However, studies of VEGF treatment in mice are inconsistent. One study found that blocking VEGF signaling in AD mice leads to better cognitive function [19], while another study found that VEGF treatment led to better cognitive function in mice [5]. In the context of Robo4, our data and previous studies suggest that the impact of VEGF treatment, whether positive or negative in AD, might depend on the status of Robo/Slit signaling.…”
Section: Vegf and Adsupporting
confidence: 56%
“…In an AD mouse model, Avastin was able to restore long-term memory, decrease glial activation, and reverse genetic changes associated with blood-brain barrier dysfunction, as seen in AD models [187]. Alternatively, in clinical trials using Avastin in patients with branch retinal vein occlusion with or without NTG, those with NTG had worsened visual acuity even with Avastin treatment.…”
Section: Vascular Flow and The Link To Ntg In Admentioning
confidence: 99%
“…Pharmaceutically available VEGF-inhibitors can be delivered as intravitreal injection treatments for neovascular AMD and diabetic macular edema (DME) [178,185]. A specific example of a VEGF-inhibitor that has been used in both treatment of AD and NTG is bevacizumab (Avastin) [186,187].…”
Section: Vascular Flow and The Link To Ntg In Admentioning
confidence: 99%